'Can I code?' Exploring rural fifth‐grade girls' programming self‐efficacy and interest in a developing country. - Liu, Yanjia; Qin, Chao; He, Hao (Journal of Computer Assisted Learning, 2024)
Background: The world is moving towards digitalization and intelligence. Programming has become an essential development competency. Even though many countries are currently making great efforts to expand programming education, the programming education in these countries shows an imbalance in geographical and gender dimensions. We found that few studies paid attention to rural girls' programming learning in developing countries. Objectives: This study focuses on programming learning among rural girls in a developing country (China) from an educational equity perspective. We investigated the level and the changes in these girls' self‐efficacy and interest in programming. Methods: We conducted a three‐month (12‐week) semester of programming teaching for rural fifth‐grade girls. Two rounds of data collection were conducted at the mid‐semester (first‐measure) and the end of the semester (second‐measure), with semi‐structured interviews at the end of the semester. Results and conclusions: The results showed that rural girls' programming self‐efficacy was at a moderate‐to‐high level and remained stable, but there were no gender differences in programming self‐efficacy between boys and girls in the second‐measure. Girls' self‐efficacy was positively correlated with interest, and programming education could help girls to increase their interest in programming, but boys and girls did not show gender differences in their programming interest in second‐measure. Interestingly, we found that girls' perceived programming knowledge acquisition was significantly higher than overall programming efficacy. Takeaways: These findings provide meaningful implications for programming education in less developed areas and female early programming education. Lay Description: What is already known about this topic: There is a significant gender imbalance in the programming field and females were severely underrepresented.Potential causes for these issues might be women's lack of confidence and interest in programming.Previous studies have shown that female college students in computer science showed insufficient confidence in programming at school, which made them avoid becoming programmers and choose other careers after graduation.Female students' low confidence and interest in programming might have already existed in their earlier studies, such as high school or even elementary school. What this paper adds: Rural fifth‐grade girls' programming self‐efficacy was at a moderately high level, with no significant differences compared to boys, and maintained a stable level throughout the entire learning period.Rural girls held a high level of programming interest at the beginning, which was reinforced by programming education, and there was no gender difference in programming interest.Rural girls' perceived programming knowledge acquisition was significantly higher than overall programming efficacy.Rural girls' self‐efficacy was positively correlated with interest. Implications for practice and/or policy: In rural areas, fifth‐grade girls and boys had approximate self‐efficacy and interest in programming.Providing early programming education to girls in rural areas can increase their interest in programming.